CBS News/New York Times Polls, 1977-1978 ([Verlag nicht ermittelbar], 1984)
This study is part of a continuing series of monthly surveys that solicit public opinion on the presidency and on a range of other political and social issues. With the exception of Part 8, June 1978 Poll -- California Sample, (for which there was no national sample), each data file in this collection represents a distinct nationwide survey that was conducted during 1977-1978. Approximately 1,000-1,500 randomly selected adults were surveyed by telephone in each poll. Respondents were asked to give their opinions of President Jimmy Carter and his handling of the presidency, foreign affairs, and the economy, as well as their views on a range of current social and economic issues such as crime, police behavior, discrimination, and working women. In addition, the July 1977 Energy Poll (Part 3) focused specifically on energy problems, exploring respondents' perceptions of the seriousness of energy shortages and who or what may have been responsible, their reactions to President Carter's proposals calling for conservation and sacrifice, and whether or not their own energy usage behavior was likely to change, particularly with regard to home heating and automobile use. The October 1977 Poll (Part 4) covered topics such as the Panama Canal treaty, the ongoing conflict in the Middle East, changing lifestyles, and the impact of the women's movement on family life. The February 1978 Poll (Part 6) dealt with the attitudes of Blacks and Whites on racial issues. Topics covered included police harassment, urban poverty, racial disturbances, segregation in neighborhoods and schools, and the portrayal of Black Americans on television. In addition to asking respondents about the efforts of Egypt and Israel to negotiate a peace agreement, the April 1978 Poll (Part 7) also covered current national issues such as inflation, unemployment, energy prices, and personal savings. California's Proposition 13 was the primary subject of the poll in Part 8, June 1978 Poll -- California Sample. Other topics included arms limitation talks between the United States and the Soviet Union, and United States' potential intervention in Africa. Background information on respondents includes voter participation history, political party affiliation, political orientation, age, sex, race, religion, education, employment, household income, and participation in labor unions.